Pengaruh Fluktuasi Suku Bunga Kredit KURS terhadap Profitabilitas - Listari, Shinta; Pardede, Robert Pius (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
The high level of business competition nowadays challenges companies to make every effort to survive and to continuously innovate in order to fulfill the customersâ€™ demands. The past few years, property industry in Indonesia experienced a tremendous development. This is shown by the increasing number of residential housing, shopping centers, even to the township. The number of Indonesian resident is a very potential market for industrial property. Property prices continue to experience a notable increase caused by a number of investors and speculators. At the end of 2013, Bank Indonesia released a policy â€œLoan To Valueâ€ to secure property prices in Indonesia, particularly the housing sector from investors and speculators game. The purpose of this study case was to determine the accounting policy of interest rates and exchange rate, to find out the recognition of loan interest rate fluctuations and exchange rate, and determine the effect of changes in interest rates and exchange rates on profitability in property companies, namely PT Summarecon Agung Tbk, PT Agung Podomoro Land Tbk, and PT Alam Sutera Realty Tbk at 5 period, 31 December 2012, 30 June 2013, 31 December 2013, 30 June 2014, and 31 December 2014. The research shows that the three companies use and apply PSAK 10 related to exchange rates and PSAK 26 related to borrowing cost, lending costs. These costs occur due to the lending rates for bank debt owned by the company. PT Summarecon Agung Tbk and PT Agung Podomoro Land Tbk included the foreign exchange differences in the statement of cash flows as the effect of exchange rate differences affecting cash and cash equivalents in the current year and PT Alam Sutera Realty Tbk included it into a foreign exchange gain/(loss) on foreign exchange that affect profitability in the current year. Mean while, credit interest rate fluctuations affect the rise in lending cost and the exchange rate is not significant according to results from SPSS calculations.